How do BMI-restrictive policies impact women seeking NHS-funded IVF in the United Kingdom? A qualitative analysis of online forum discussions - Rebecca Muir; Meredith K. D. Hawking (BMC, 2024)
Plain English Summary In the United Kingdom, people can access public funding for In Vitro Fertilisation (IVF) treatment if certain criteria are met. Funding restrictions differ between geographical areas, but most areas restrict treatment to women with a Body Mass Index (BMI) below 30. This study explores the unexpected and unintended harms experienced by women restricted from NHS-funded IVF due to these BMI criteria. Posts from a popular infertility online forum were collected and thematically analysed. The study found moralising discourses around body weight which emphasized that women had personal control over their bodies and needed to 'work' to change their bodies to show deservingness for treatment. We conclude that NHS-IVF policies in the UK overlook the emotional and moral burdens placed on individuals due to rigid BMI criteria. As the impact of BMI limits on healthcare access is an under-researched topic, we believe this work is important for demonstrating the harms of BMI-restrictive policies.